2018
DOI: 10.18520/cs/v114/i06/1241-1249
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Soil Nutrient Information System:Study from the North East Region of India

Abstract: Soil fertility has direct implications on the agricultural production scenarios of a region. Surface soil samples at 1 km grid were collected to assess the fertility status of Lakhimpur district (Assam) in North East India. Fertility parameters like soil organic carbon, available nitrogen, phosphorus, potassium, iron, manganese, zinc and copper were determined using standard analytical procedure. Spatial distribution maps of the soil parameters were generated using regularized spline method in ArcGIS 10.0. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most researches showed that parent material has the most significant effect on soil formation and soil nutrient content, and soil nutrient content is also closely related to climate, rainfall, vegetation, land use types and agricultural production measures [43]. It is well known that soil parent materials are the material carriers and there are differences in soil nutrients for the difference of parent materials [2,19,43]. It commonly existed a significant correlation between parent material and soil nutrients, that is, the higher the mineral element content of soil parent material, the higher the content of plant nutrients in soil in the corresponding area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most researches showed that parent material has the most significant effect on soil formation and soil nutrient content, and soil nutrient content is also closely related to climate, rainfall, vegetation, land use types and agricultural production measures [43]. It is well known that soil parent materials are the material carriers and there are differences in soil nutrients for the difference of parent materials [2,19,43]. It commonly existed a significant correlation between parent material and soil nutrients, that is, the higher the mineral element content of soil parent material, the higher the content of plant nutrients in soil in the corresponding area.…”
Section: Discussionmentioning
confidence: 99%
“…Soil nutrients are important indicators of cultivated land quality, which is determined by two aspects: soil fertility and spatial location [1]. Soil fertility, which is closely related to the concentrations of soil nutrient elements, is the foundation of soil productivity [2]. Soil nutrient elements can be classified into essential, beneficial, and toxic elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimapur district level data from Eri and Muga farms were designed in MS Excel and generated as a point layer in ArcGIS 10.3 comprising all the nutrient availability information in the attribute table. The regularised spline interpolation technique was employed for the point data to create spatial distribution layers for soil pH; organic carbon; and available N, P, K, S, B, Fe, Mn, Zn and Cu in a GIS environment [1,8,22,23]. The layers were categorised with their threshold values.…”
Section: Data Interpretation In Gis Environmentmentioning
confidence: 99%